Development of persistent headache following stroke: A 3-year follow-up. (April 2015) - Hansen, Anne P; Marcussen, Ninna S; Klit, Henriette; Kasch, Helge; Jensen, Troels S; Finnerup, Nanna B
Background: Headache following stroke has been described in previous studies with an incidence of 23%–54%, but a clear description of headache developing after stroke onset is still lacking. The aim of this study was to determine the incidence and characteristics of persistent novel headache after stroke and to describe the use of medication, including dipyridamole. Methods: As a follow-up to a prospective study, a standardized questionnaire about characteristics of novel headache and medication use was sent out to surviving patients three years after their stroke. Results: The questionnaire was sent to 256 patients and returned by 222, of whom 12% (26/222) of patients reported persistent novel headache. Dipyridamole had no significant influence on the incidence. Stroke-attributed headache according to predefined criteria was reported in 7.2% (16/222) of patients, with tension-type-like headache in 50.0%, migraine-like in 31.3% and medication overuse in 6.25% of patients. More than half of patients experienced moderate to severe pain and had a score of 55 or above on the Headache Impact Test-6 scale. Conclusion: Novel headache after stroke affects one in 10 patients and seems to be unrelated to dipyridamole use. Persistent headache attributed to stroke is similar to tension-type headache for half of patients.